Memory Void: Digital Games Preservation in Portugal - Lima, Luciana; Mota, Ana Teresa (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
Some collective efforts to preserve and disseminate Portuguese digital games are led by retro gaming communities and have contributed to the emergence of other narratives about the history of video games in the last decade in Portugal. In this paper, we present two of these communities, namely Planeta Sinclair and RetroArquivo, and examine how their preservation activity can be a way to promote the recognition of the cultural, historical, and material values of old games. We conclude that digital game preservation is mostly contained in an informal and networked infrastructure, within which archival libraries of these same artifacts are developed.